Physiotherapist‐led suprascapular nerve blocks for persistent shoulder pain: Evaluation of a new service in the UK. (13th July 2017) - Salt, E.; van der Windt, D. A.; Chesterton, L.; Mainwaring, F.; Ashwood, N.; Foster, N. E.
Abstract: Introduction: This service evaluation explored and reported findings from a new physiotherapist‐led service offering suprascapular nerve blocks (SSNBs) to patients with persistent shoulder pain. Methods: We collected data before the SSNB injection and at the 6‐weeks and 6‐month follow‐up from consecutive patients with persistent shoulder pain being treated by physiotherapists or an anaesthetist. Outcomes were patient‐reported pain (numerical rating scale [NRS 0 to 10]), patient‐specific functional score (PSFS) and health‐related quality of life [the EuroQol five dimensions questionnaire (EQ5D‐5 L)]. Exploratory analyses compared baseline and follow‐up scores within each clinician delivery group (physiotherapists, anaesthetist). Results: Forty patients (mean age 57 years [standard deviation SD 12]; 63% female) received an SSNB from a physiotherapist, eight patients (mean age 59 years [SD 11]; female 88%) received an SSNB from an anaesthetist. At the 6‐week follow‐up, the physiotherapy group showed a mean reduction in pain (on the NRS): 2.2 (95% confidence interval [CI] 1.3 to 3.0) and an improvement in function (on the PSFS): –1.3 (95% CI –1.9 to −0.4). Similar changes were found in those treated by the anaesthetist (pain: 1.3 [95% CI –1.18 to 3.80]; function: –1.4 (95% CI –3.18 to 0.35]). Very small changes, that were not statistically significant, were found in EQ5D‐5 L scores. At the 6‐month follow‐up, the mean reduction in pain (NRS) was maintained at 2.0 (95% CI 0.99 to 2.95) for the physiotherapy group. Conclusion: The results provide early, exploratory evidence that patients with persistent shoulder pain treated by physiotherapists using palpation‐guided SSNBs achieve clinically important changes in pain and function in the short and medium term.